Analisis Kualitas Pelayanan Publik pada Kantor Kecamatan Pamenang - Habazoh; Fahmi Rasyid; Mani Festati Broto (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This research was motivated by the central government's program, namely the creation of e-KTP for all Indonesian citizens. As a form of public service, people want fast and satisfying services. Meanwhile, the reality of the services received by the community is far from what was expected, and the low quality of e-KTP services such as the manufacture of e-KTP for days and the inadequacy of the devices used in serving. This research uses a qualitative-descriptive method, intended to provide an overview and analyze community services at the Pamenang District Office. Data were collected through questionnaires and interviews. The results showed that the quality of public services at the Pamenang Subdistrict Office was still not optimal, which can be seen from the guarantee of uncertain settlement, inadequate facilities and infrastructure, lack of attention and good response from employees, lack of responsiveness of employees and lack of information provided to the community regarding service procedures. The employees have also not been consistent in implementing the Pamenang Sub-district Decree Number 11 of 2020 concerning Standard Operating Procedures which aims to realize quality services.